No significant difference in the prognostic value of the 5th and 7th editions of AJCC staging for differentiated thyroid cancer. (4th February 2014) - Vrachimis, Alexis; Gerss, Joachim; Stoyke, Maren; Wittekind, Christian; Maier, Tobias; Wenning, Christian; Rahbar, Kambiz; Schober, Otmar; Riemann, Burkhard
Summary Objective The seventh edition of the American Joint Committee on Cancer (AJCC) has more detailed staging categories for differentiated thyroid cancer (DTC) than the fifth edition. The aim was to compare potential alterations in the disease‐specific (DSS), event‐free (EFS) and overall survival (OS), after reclassification from the fifth to the seventh edition. Methods Data of 2460 patients with DTC referred to our centre were reclassified from the fifth to the seventh edition of AJCC. DSS, EFS and OS were calculated using the Kaplan‐Meier method and compared by the log‐rank test. The relative abilities of each edition to predict survival were calculated by the proportion of variance explained (PVE). Results After reclassification to the seventh edition, there was an increase in stage I and IV patients from 58·1% to 65·0% and from 6·2% to 10·1%, respectively, and a corresponding decrease in stage II and III patients from 22·4% to 12·5% and 13·3% to 12·4%, respectively. As to DSS, the seventh edition had only a marginally higher PVE value than the fifth edition. With respect to EFS, the predictability of the seventh edition was even inferior to that of the fifth edition. Similarly, with regard to OS, the PVE value was slightly better for the older edition. Furthermore, a comparison only for those patients affected by the reclassification revealed no differences for DSS, EFS or OS between classifications. Conclusion When comparing the stages of the seventh with the fifth edition of the AJCC for DTC, there was no significant difference in predicting DSS, EFS and OS.